Strategy For Implementing Isolation Precautions in The Hemodialysis Services At The HD Clinic of Nitipuran During the Period of Covid-19 Pandemic - Murnani, Sari; Dewi, Arlina (Universitas Aisyah Pringsewu, 2021)
COVID-19 outbreak is a challenge for health facilities in providing guarantees for patient safety and works safety. The dialysis clinic has a high risk and vulnerable environment to the spread of COVID-19, but it has to keep providing services to patients with chronic kidney disease. One way to ensure quality and patient safety is to apply isolation precautions. This type of study was is mixed-method research, with a sequential explanatory approach. The population in this study was nurses and doctors at the HD Clinic of Nitipuran. The sampling technique in the quantitative research used total sampling; while qualitative research used the purposive sampling technique. Quantitative data analysis was Spearman rank analysis, while qualitative research used Miles and Huberman analysis. The behavior of implementing isolation precautions in the hemodialysis services at the HD Clinic of Nitipuran was carried out more strictly, supported by a high level of hygiene awareness, supervision and management support. However, the high workload and inadequate infrastructure are obstacles was carried out isolation precautions. Factors related to the behavior of isolation precautions were namely education, knowledge, training, attitudes, cultural values, motivation, supervision, management support and environmental facilities. The strategy for implementing isolation precautions was namely the SO strategy was in the first quadrant which had the highest score, with priorities in making policies and efforts to prevent post-exposure infections, increasing the efficiency of facilities and infrastructure and always reviewing policies and internal guidelines.Abstrak: Wabah COVID-19 menjadi tantangan bagi fasilitas kesehatan dalam memberikan jaminan keselamatan pasien dan keselamatan kerja. Klinik dialysis memiliki lingkungan yang berpotensi tinggi dan rawan penyebaran COVID-19, namun harus tetap memberikan pelayanan pada penderita penyakit ginjal kronik. Salah satu cara untuk menjamin mutu dan keselamatan pasien adalah dengan menerapan kewaspadaan isolasi. Jenis penelitian ini merupakan jenis penelitian mix method, dengan pendekatan sequential explanatory. Populasi dalam penelitian ini adalah perawat dan dokter klinik HD Nitipuran. Teknik sampling pada penelitian kuantitatif menggunakan total sampling dan penelitian kualitatif menggunakan teknik purposive sampling. Analisis data kuantitatif dengan analisis spearman rank, sedangkan penelitian kualitatif menggunakan analisis miles and huberman. Perilaku penerapan kewaspadaan isolasi pada pelayanan hemodialysis di Klinik HD Nitipuran dilakukan lebih ketat, didukung kesadaran kebersihan dan pengawasan serta dukungan manajemen yang tinggi. Beban kerja yang tinggi dan sarana prasana yang belum memadai menjadi penghambat dalam melakukan kewaspadaan isolasi. Faktor yang berhubungan dengan perilaku kewaspadaan isolasi yaitu factor pendidikan, pengetahuan, pelatihan, sikap, nilai budaya, motivasi, supervise, dukungan manajemen dan sarana lingkungan. Strategi penerapan kewaspadaan isolasi diketahui bahwa strategi SO berada di kuadran pertama memiliki skor tertinggi, dengan prioritas membuat kebijakan dan upaya dalam pencegahan terjadinya infeksi paska pajanan, meningkatkan daya guna fasilitas sarana dan prasarana serta selalu melakukan peninjauan kembali terkait kebijakan dan pedoman internal.